Micro-arc oxidation method of titanium-based pollution discharge equipment
By using Cu(P2O7)26- complex ions as the copper source and controlling the pH value of the electrolyte in the micro-arc oxidation process, the problem of insufficient Cu doping in the micro-arc oxidation film of titanium-based sewage discharge equipment is solved, achieving efficient copper doping and film densification, improving the antifouling and corrosion resistance of titanium-based sewage discharge equipment, and making it suitable for marine pipeline systems.
Patent Information
- Application Number
- CN202511943717.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-22
- Publication Date
- 2026-01-30
AI Technical Summary
In existing micro-arc oxidation processes, the Cu doping content in the micro-arc oxidation film layer of titanium-based sewage discharge equipment is insufficient, resulting in poor antifouling performance. Furthermore, existing improvement methods are costly and inefficient, making it difficult to meet the corrosion resistance and antifouling requirements of sea-access pipeline systems.
Using Cu(P2O7)26- complex ions as the copper source, and controlling the electrolyte pH value at 8.5~8.8, a copper-doped micro-arc oxidation film is formed on the surface of a titanium-based workpiece through micro-arc oxidation. The pyrophosphate is decomposed at high temperature to generate phosphate deposits, thereby improving the film density and copper content.
It significantly improves the copper content and antifouling performance of the micro-arc oxidation film, reduces defects, and enhances the corrosion resistance and antifouling ability of the film, making it suitable for large-scale industrial production.
Smart Images

Figure CN121428636A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials surface treatment engineering, and specifically relates to a micro-arc oxidation method for titanium-based sewage discharge equipment. Background Technology
[0002] In recent years, due to the excellent comprehensive properties of titanium and its alloys, they have been increasingly used in the manufacture of key components (pipes, valves, flanges, etc.) of sewage pipeline systems, particularly in marine pipeline systems. However, the internal environment of marine pipeline systems is harsh, typically containing complex microorganisms and high concentrations of inorganic salts, as well as sediment and gravel, which can lead to the failure of titanium-based equipment, causing a series of problems such as pipe blockage, leakage, and pollution. Therefore, to address the problems faced by titanium-based sewage equipment used in marine pipeline systems, it is necessary to develop relevant surface treatment processes to improve their antifouling capabilities and corrosion resistance.
[0003] Micro-arc oxidation (MAO) is a surface oxidation film formation process based on arc discharge. It typically relies on the matching and adjustment of electrolyte and electrical parameters, utilizing the instantaneous high temperature and pressure generated by the arc discharge to grow a micro-arc oxide film in situ on the surface of valve metals, including titanium and its alloys. This film has high hardness, forms a metallurgical bond with the substrate, exhibits high interfacial bonding strength, and possesses high chemical inertness, effectively blocking external corrosive environments and demonstrating good corrosion resistance. Currently, micro-arc oxidation typically uses an electrolyte containing copper ions to directly obtain Cu doping into the micro-arc oxide film on the surface of titanium or its alloys. However, due to the migration of copper ions to the cathode caused by the applied electric field, the Cu doping amount in the micro-arc oxide film is severely insufficient, affecting its antifouling performance. Therefore, it is necessary to improve the existing micro-arc oxidation process to enhance the antifouling performance of the micro-arc oxide film. Summary of the Invention
[0004] To address the aforementioned issues, this invention provides a micro-arc oxidation method for titanium-based sewage discharge equipment. While ensuring the growth of the micro-arc oxidation film, it increases the Cu doping amount and reduces related defects, ultimately achieving a simultaneous improvement in the anti-fouling and corrosion resistance properties of the micro-arc oxidation film.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows.
[0006] This invention provides a micro-arc oxidation method for titanium-based sewage discharge equipment, comprising the following steps: Cu(P2O7)2 in the electrolyte 6- As a copper source, a titanium-based workpiece is used as the anode and an inert electrode is used as the cathode for micro-arc oxidation to obtain a copper-doped micro-arc oxidation film on the surface of the titanium-based workpiece; the titanium-based workpiece is a sewage pipe in a titanium-based sewage discharge equipment, specifically, the sewage pipe is a pipe in a marine pipeline system, and its material is titanium alloy. Cu(P2O7)2 in the electrolyte 6- The concentration of the electrolyte is 0.005 mol / L to 0.05 mol / L, and the pH of the electrolyte is 8.5 to 8.8.
[0007] In this invention, Cu(P2O7)2 6- As a copper source, and by controlling the pH of the electrolyte to 8.5–8.8, the Cu(P₂O₇)₂ solution is ensured to... 6- The stability of the complex ions and the film-forming properties after micro-arc oxidation. Copper pyrophosphate itself is a solid particle, and direct application of the electrolysis process results in a very low copper doping level. Therefore, this invention obtains stable Cu(P2O7)2 by adding potassium pyrophosphate and copper pyrophosphate, controlling the pH range to 8.5~8.8. 6- The complex ion structure enables a significant increase in the copper doping content in the resulting micro-arc oxide film.
[0008] In another preferred embodiment, the concentrations of each component in the electrolyte are as follows: 0.01 mol / L~0.02 mol / L copper pyrophosphate, 0.5 mol / L~0.9 mol / L potassium pyrophosphate, 0.01 mol / L~0.02 mol / L potassium phosphate, 0.05 mol / L~0.06 mol / L sodium dihydrogen phosphate; The electrolyte also includes the addition of disodium hydrogen phosphate to adjust the pH of the electrolyte to 8.5-8.8.
[0009] In another preferred embodiment, when the titanium-based workpiece is made of TC4, the concentrations of each component in the electrolyte are as follows: 0.01 mol / L copper pyrophosphate, 0.5 mol / L potassium pyrophosphate, 0.01 mol / L potassium phosphate, 0.05 mol / L sodium dihydrogen phosphate.
[0010] In another preferred embodiment, when the titanium-based workpiece is made of TA1, the concentrations of each component in the electrolyte are as follows: 0.02 mol / L copper pyrophosphate, 0.56 mol / L potassium pyrophosphate, 0.01 mol / L potassium phosphate, and 0.06 mol / L sodium dihydrogen phosphate.
[0011] In another preferred embodiment, the titanium-based workpiece is made of TA3, and the concentrations of each component in the electrolyte are as follows: 0.02 mol / L copper pyrophosphate, 0.90 mol / L potassium pyrophosphate, 0.02 mol / L potassium phosphate, 0.06 mol / L sodium dihydrogen phosphate.
[0012] In another preferred embodiment, the parameters of the micro-arc oxidation are as follows: operating voltage of 400V~800V, preferably 600V; operating frequency of 100Hz~1000Hz; and current density of 0.02A / cm. 2 ~0.80A / cm 2 The duty cycle is 10%~60%, the processing time is 5min~30min, and the reaction temperature is 10℃~50℃.
[0013] In another preferred embodiment, the titanium alloy further includes TA2, Ti-Ni, Ti-2Al-2.5Zr, Ti-32Mo, and Ti-Mo-Ni.
[0014] In another preferred embodiment, the titanium-based workpiece is further subjected to degreasing, polishing, cleaning, and drying before micro-arc oxidation.
[0015] In another preferred embodiment, the inert electrode is any one of platinum sheet, graphite, or stainless steel.
[0016] In another preferred embodiment, the distance between the anode and the cathode is 3cm to 20cm.
[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention utilizes the copper pyrophosphate complex ion Cu(P2O7)2 6- Using copper as the source, a titanium-based workpiece is used as the anode for micro-arc oxidation, and an inert electrode is used as the cathode. Due to Cu(P₂O₇)₂ 6- The complex ion is sensitive to pH; the pH of the electrolyte must be stable between 8.5 and 8.8 to allow Cu(P₂O₇)₂ to function properly. 6- It exists stably; if it deviates from this range, it will precipitate as solid Cu₂P₂O₇ or positively charged Cu. 2+ The existence of this form significantly reduces work efficiency. Under the influence of an external electric field, Cu(P2O7)2 6- The directional electromigration of complex ions onto the surface of titanium-based workpieces significantly increases the Cu content on the titanium surface. Pyrophosphate decomposes at the high temperature of arc discharge to obtain phosphate deposits, further enhancing the density of the micro-arc oxide film. Furthermore, the entire process does not generate a large amount of gas, thus reducing defect formation and promoting the growth and densification of the micro-arc oxide film. The addition of copper pyrophosphate and potassium pyrophosphate also ensures the stability of Cu(P₂O₇)₂. 6- The content of complex ions is stable.
[0018] This invention utilizes sodium hydrogen phosphate and disodium hydrogen phosphate to effectively stabilize the pH value between 8.5 and 8.8, minimizing its impact on arc initiation and thus ensuring the stability of the electrolyte and reaction interface, promoting the stable progress of the micro-arc oxidation reaction. The addition of potassium phosphate acts as a buffer to some extent and accelerates the micro-arc oxidation reaction. Attached Figure Description
[0019] Figure 1 The image shows a comparison of the surface morphology and Cu doping content of the micro-arc oxidation film prepared in Example 1.
[0020] Figure 2 The image shows a comparison of the low-frequency impedance modulus of the micro-arc oxidation film prepared in Example 1.
[0021] Figure 3 The image shows a comparison of the inhibitory effects of the micro-arc oxidation film layer prepared in Example 1 on the growth of SRB bacteria.
[0022] Figure 4 The image shows a comparison of the surface morphology and Cu doping content of the micro-arc oxide film prepared in Example 2.
[0023] Figure 5 This is a comparison chart of the low-frequency impedance modulus of the micro-arc oxidation film prepared in Example 2.
[0024] Figure 6 The image shows a comparison of the inhibitory effect of the micro-arc oxidation film layer prepared in Example 2 on the growth of SRB bacteria.
[0025] Figure 7 The image shows a comparison of the surface morphology and Cu doping content of the micro-arc oxide film prepared in Example 2.
[0026] Figure 8 The image shows a comparison of the low-frequency impedance modulus of the micro-arc oxidation film prepared in Example 3.
[0027] Figure 9 The image shows a comparison of the inhibitory effect of the micro-arc oxidation film layer prepared in Example 3 on the growth of SRB bacteria.
[0028] Figure 10 This is a schematic diagram of the micro-arc oxidation process. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0030] This invention provides a micro-arc oxidation method for titanium-based sewage discharge equipment, the method comprising: reacting negatively charged copper pyrophosphate complex ions Cu(P2O7)2 6- Using titanium and aluminum-based workpieces as the copper source, micro-arc oxidation is performed with an inert electrode as the cathode to obtain a copper-doped micro-arc oxide film. The titanium-based workpieces are titanium or titanium alloys, and are components of sewage pipeline systems, primarily targeting marine pipeline systems. The resulting micro-arc oxide film exhibits good corrosion resistance and antifouling properties. A schematic diagram of the micro-arc oxidation process is shown below. Figure 10 As shown; in this embodiment of the invention, the negatively charged copper pyrophosphate complex ions Cu(P2O7)2 in the micro-arc oxidation electrolyte are used. 6- As a copper source; Cu(P2O7)2 6- The concentration of the complex ion is 0.002 mol / L to 0.05 mol / L, and the pH of the electrolyte is maintained between 8.5 and 8.8.
[0031] In this embodiment of the invention, prior to micro-arc oxidation, the process further includes: degreasing, polishing, cleaning, and drying the titanium-based workpiece. Specifically, this involves progressive polishing with sandpaper, cleaning with acetone, and drying.
[0032] In this embodiment of the invention, the parameters for micro-arc oxidation are as follows: operating voltage of 400V~800V, preferably 600V; operating frequency of 100Hz~1000Hz; and current density of 0.02A / cm². 2 ~0.80A / cm 2 The duty cycle is 10%–60%, the processing time is 5–30 min, and the reaction temperature is 10℃–50℃. Using these parameters, the micro-arc oxidation film can achieve good performance.
[0033] In this embodiment of the invention, the titanium alloy is any one of TA1, TA2, TA3, TC4, Ti-Ni, Ti-2Al-2.5Zr, Ti-32Mo, and Ti-Mo-Ni.
[0034] In this embodiment of the invention, if the titanium-based workpiece is made of TC4, the concentrations of each component in the electrolyte are as follows: 0.01 mol / L copper pyrophosphate, 0.5 mol / L potassium pyrophosphate, 0.01 mol / L potassium phosphate, and 0.05 mol / L sodium dihydrogen phosphate; and disodium hydrogen phosphate is added to ensure the pH is between 8.5 and 8.8. The selection of pH value mainly considers the presence of pyrophosphate and the hydrolysis of phosphate, hydrogen phosphate, and aluminum ions dissolved from TC4.
[0035] In this embodiment of the invention, if the titanium-based workpiece is made of TA1, the concentrations of each component in the electrolyte are as follows: 0.02 mol / L copper pyrophosphate, 0.56 mol / L potassium pyrophosphate, 0.01 mol / L potassium phosphate, and 0.06 mol / L sodium dihydrogen phosphate; and disodium hydrogen phosphate is added to ensure the pH is between 8.5 and 8.8. The selection of pH value mainly considers the existence form of pyrophosphate and the hydrolysis of phosphate and hydrogen phosphate ions.
[0036] In this embodiment of the invention, if the titanium-based workpiece is made of TA3, the concentrations of each component in the electrolyte are as follows: 0.02 mol / L copper pyrophosphate, 0.90 mol / L potassium pyrophosphate, 0.02 mol / L potassium phosphate, and 0.06 mol / L sodium dihydrogen phosphate; and disodium hydrogen phosphate is added to ensure the pH is between 8.5 and 8.8. Sodium hydroxide and potassium dihydrogen phosphate can adjust the pH of the micro-arc oxidation electrolyte, which is beneficial for film formation.
[0037] In this embodiment of the invention, the inert electrode is any one of platinum sheet, graphite or stainless steel.
[0038] The distance between the micro-arc oxidation anode and the micro-arc oxidation cathode is 3cm to 20cm.
[0039] Currently, to improve antifouling performance, high concentrations of Cu (0.13~3.2 mol / L) are commonly used. 2+ Micro-arc oxidation is performed using an electrolyte containing ions to directly obtain a Cu-doped micro-arc oxidation film on the surface of titanium or its alloys. However, due to the applied electric field, Cu... 2+ Ions migrate to the cathode, resulting in a severe deficiency of Cu doping and affecting the lifespan of the micro-arc oxidation cathode.
[0040] To address the aforementioned issues, related studies have proposed using neutral Cu₂O or Cu nanoparticles as the Cu source, increasing the particle concentration in the electrolyte to enhance the Cu content doped into the micro-arc oxidation film. However, this method, employing nanoparticles, is not only costly and has low Cu source utilization, but also offers limited improvement in Cu doping content within the micro-arc oxidation film, with copper doping levels using Cu nanoparticles ranging from 1.3 wt% to 2.76 wt%. Other studies have used negatively charged Cu-EDTA complex ions as the Cu source, leveraging the electromigration effect of an applied electric field to effectively improve Cu source utilization and increase the Cu doping content to some extent, with copper doping levels ranging from 0.42 wt% to 1.51 wt%. However, when the concentration of Cu-EDTA complex ions reaches above 10 g / L, it inhibits arc initiation, thereby affecting the normal growth of the micro-arc oxidation film and leading to poor film uniformity. Furthermore, EDTA complex ions are prone to decomposition under the transient high temperatures caused by arc initiation, producing gases such as CO2 and NOx. This not only affects the solution environment and thus film growth but also causes related pores in the film, affecting its structure. Simultaneously, Cu-EDTA complex ions are not common chemical raw materials, resulting in high costs and hindering large-scale industrial production. Therefore, existing technologies using micro-arc oxidation struggle to address the problems of low Cu source utilization, low Cu doping levels, numerous defects, and high costs. Consequently, they are ill-suited to the corrosion resistance and antifouling properties required for sewage treatment equipment, limiting the application of titanium-based pipeline equipment in large-scale sewage pipeline systems, particularly in marine pipeline systems.
[0041] However, existing technologies for evaluating Cu doping content are not uniform. On one hand, different identification methods significantly affect the Cu content detection results. This is mainly because existing technologies typically use weight percentage to detect Cu content, but the weight percentage is affected by the composition of the film itself. For example, in the system of this invention, the adsorption of phosphate, K ions, and Na ions significantly affects the Cu content obtained based on compositional analysis. In other systems, such as silicates, aluminates, and tungstates, even with identical Cu doping content, the Cu content obtained based on compositional analysis will differ due to the substrate. On the other hand, electrical parameters have a significant impact on the copper doping content; for example, Cu... 2+ Ions are highly dependent on the instantaneous enrichment effect caused by negative current or cathodic polarization. However, in the system of this invention and the system using a negatively charged Cu source, positive current is used throughout the process, and it does not depend on negative current. From the above analysis, it can be seen that current Cu content calculations are all relative; there is no effective method to obtain absolute content, and it is greatly affected by the environment and process.
[0042] This invention proposes a novel copper source for micro-arc oxidation processes, employing Cu(P2O7)2 in the form of complex ions. 6-Using copper as the source and precisely controlling the electrolyte pH to remain stable between 8.5 and 8.8, the Cu(P2O7)2... 6- The copper pyrophosphate complex exhibits excellent stability, enabling stable migration towards the anode under an applied electric field. This effectively increases the copper content on the cathode surface, resulting in a copper content in the micro-arc oxidation film ranging from 2.5 wt% to 3.2 wt%. Simultaneously, the copper pyrophosphate complex possesses a strong buffering effect, ensuring pH stability at the solution and reaction interface while minimizing its impact on arc initiation, thus promoting the formation of a high-Cu micro-arc oxidation film. The pyrophosphate decomposes into solid phosphate at the high temperature of the arc discharge, minimizing gas generation and reducing defects caused by gas release. As a precipitate in the micro-arc oxidation ceramic film, it promotes film growth, further preventing defect formation and enhancing physical barrier properties, significantly improving corrosion resistance. Furthermore, the copper pyrophosphate, potassium pyrophosphate, and related additives used in this invention are common chemical raw materials widely used in the electroplating industry. These raw materials are readily available and inexpensive, requiring minimal equipment and allowing for large-scale industrial production based on existing production lines.
[0043] The technical solution of this invention requires only one micro-arc oxidation process to prepare a micro-arc oxidation film with high copper content. On the basis of the high corrosion resistance and high wear resistance of the micro-arc oxidation film, the anti-fouling ability is enhanced, laying the foundation for the large-scale application of titanium-based materials in sewage pipeline systems, especially in marine pipeline systems.
[0044] To further illustrate the solutions provided in the embodiments of the present invention, specific technical solutions can be found in the following embodiments.
[0045] Example 1: A micro-arc oxidation method for a titanium-based sewage discharge device, comprising the following steps: S1. Using TC4 as the substrate, clean and degrease the TC4 workpiece, then polish it step by step with sandpaper, clean it with acetone and dry it; wrap the treated TC4 workpiece with insulating tape to ensure that the reaction area size is 20mm×20mm.
[0046] S2. The molar concentrations of each raw material in the electrolyte are as follows: 0.01 mol / L copper pyrophosphate, 0.5 mol / L potassium pyrophosphate, 0.01 mol / L potassium phosphate, 0.05 mol / L sodium dihydrogen phosphate, and disodium hydrogen phosphate is added to ensure the pH is between 8.5 and 8.8 to obtain the electrolyte; in this embodiment, the pH value is specifically 8.52; the electrolyte is thoroughly stirred using a magnetic stirrer to ensure uniform dispersion.
[0047] S3. Using the pretreated TC4 workpiece as the anode and stainless steel as the cathode, connect the anode and cathode to a pulse power supply (power supply for micro-arc oxidation); the distance between the cathode and anode plates is 6 cm, and they are placed in the electrolyte mentioned above; set the micro-arc oxidation parameters: current density is 0.08 A / cm². 2 The frequency is 600Hz, the total duty cycle is 20%, the temperature is 30℃, and the time is 600s.
[0048] S4. After the reaction is complete, take out the workpiece with the micro-arc oxidation film layer (ceramic film layer), rinse it with deionized water, and let it air dry naturally to obtain a high copper content micro-arc oxidation film layer with excellent anti-fouling properties; wherein, the copper doping content is 1.7wt%.
[0049] In this embodiment, Figure 1 The image shows the surface morphology of the micro-arc oxidation film formed in Example 1. Figure 1 As shown, the micro-arc oxidation film is a porous film, and the external magnetic field has no significant effect on the morphology of the micro-arc oxidation film. The morphology image is obtained by scanning electron microscopy (SEM), and the corresponding Cu content is obtained by XRF technology. When inserted into the corresponding SEM image, it can be seen that copper pyrophosphate complex ions can be used as a copper source to prepare Cu-rich ceramic films. Figure 2 The low-frequency (0.01Hz) impedance modulus comparison diagram of the micro-arc oxidation film prepared in Example 1 shows that the addition of potassium copper pyrophosphate complex ions promotes the corrosion resistance of the obtained micro-arc oxidation film to be higher than that of the film prepared by conventional process. Figure 3 This is a comparison chart showing the antifouling capabilities of the micro-arc oxidation film prepared in Example 1 against common sulfate-reducing bacteria in sewage systems. Figure 3 As shown, the addition of copper pyrophosphate complex ions results in a micro-arc oxidation film with superior antifouling properties.
[0050] Example 2: A micro-arc oxidation method for a titanium-based sewage discharge device, comprising the following steps: S1. Degrease and clean the TA1 workpiece, then polish it step by step with 600#, 1000#, 1500#, and 2000# SiC sandpaper. Clean it with acetone and then dry it. Wrap the workpiece with insulating tape to ensure that the reaction area is 10mm×10mm.
[0051] S2. Prepare a micro-arc oxidation solution with the following mass concentrations: 0.02 mol / L copper pyrophosphate, 0.56 mol / L potassium pyrophosphate, 0.01 mol / L potassium phosphate, 0.06 mol / L sodium dihydrogen phosphate, and disodium hydrogen phosphate. Ensure the pH is between 8.5 and 8.8. In this embodiment, the pH is specifically 8.58. Stir thoroughly with a magnetic stirrer to ensure the electrolyte is evenly dispersed.
[0052] S3. Using the pretreated TA1 workpiece as the anode and stainless steel as the cathode, connect the anode and cathode to a pulse power supply, with a distance of 12cm between the anode and cathode plates, and place them in the aforementioned electrolyte; set the parameters for micro-arc oxidation: current density 0.12A / cm². 2 The frequency is 100Hz, the total duty cycle is 20%, the temperature is 30℃, and the time is 300s; S4. After the reaction is complete, take out the workpiece with the micro-arc oxide film layer, rinse it with deionized water, and let it air dry naturally to obtain a high copper content micro-arc oxide film layer with excellent anti-fouling properties; wherein, the copper doping content is 2.3wt%.
[0053] In this embodiment, Figure 4 The image shows the surface morphology of the micro-arc oxidation film prepared in Example 2, with its copper content interpolated. Figure 4 As shown, copper pyrophosphate complex ions can be used as a copper source to prepare Cu-rich ceramic films. Figure 5 The image shows a comparison of the 0.01Hz low-frequency impedance modulus of the micro-arc oxidation film prepared in Example 2. It can be seen that the addition of potassium copper pyrophosphate complex ions promotes the corrosion resistance of the obtained micro-arc oxidation film to be higher than that of films prepared by conventional processes. Figure 6 The image shows a comparison of the antifouling capabilities of the micro-arc oxidation film prepared in Example 2 against sulfate-reducing bacteria. It can be seen that the addition of potassium copper pyrophosphate complex ions promotes the superior antifouling performance of the obtained micro-arc oxidation film.
[0054] Example 3: A micro-arc oxidation method for a titanium-based sewage discharge device, comprising the following steps: S1. Degrease and clean the TA3 workpiece, then grind it step by step, clean it with acetone and dry it; wrap the workpiece with insulating tape to ensure that the reaction area size is 15mm×15mm.
[0055] S2. Prepare the micro-arc oxidation solution with the following mass concentration: The micro-arc oxidation electrolyte is prepared from 0.02 mol / L copper pyrophosphate, 0.90 mol / L potassium pyrophosphate, 0.02 mol / L potassium phosphate, 0.06 mol / L sodium dihydrogen phosphate, and disodium hydrogen phosphate, ensuring the pH is between 8.5 and 8.8. In this embodiment, the pH value is specifically 8.71. Stir thoroughly with a magnetic stirrer to ensure the electrolyte is evenly dispersed.
[0056] S3. Using the pretreated TA3 workpiece as the anode and stainless steel as the cathode, connect the anode and cathode to a pulse power supply, with a distance of 12cm between the anode and cathode plates, and place them in the aforementioned electrolyte; set the micro-arc oxidation parameters: current density 0.15A / cm². 2 The frequency is 1000Hz, the total duty cycle is 10%, the temperature is 30℃, and the time is 1000s.
[0057] S4. After the reaction is complete, take out the workpiece with the micro-arc oxide film layer, rinse it with deionized water, and let it air dry naturally to obtain a high copper content micro-arc oxide film layer with excellent anti-fouling performance; the copper doping content is 2.5wt%.
[0058] In this embodiment, Figure 7 The image shows the surface morphology of the micro-arc oxidation film prepared in Example 3, with its copper content interpolated. Figure 7 As shown, copper pyrophosphate complex ions can be used as a copper source to prepare Cu-rich ceramic films. Figure 8 The image shows a comparison of the 0.01Hz low-frequency impedance modulus of the micro-arc oxidation film prepared in Example 3. It can be seen that the addition of potassium copper pyrophosphate complex ions promotes the corrosion resistance of the obtained micro-arc oxidation film to be higher than that of films prepared by conventional processes. Figure 9 The image shows a comparison of the antifouling capabilities of the micro-arc oxidation film prepared in Example 3 against sulfate-reducing bacteria. It can be seen that the addition of potassium copper pyrophosphate complex ions promotes the superior antifouling performance of the obtained micro-arc oxidation film.
[0059] This invention uses Cu(P2O7)2 6- As a copper source, and to ensure the pH of the electrolyte is between 8.5 and 8.8, this is mainly because a slight deviation in pH affects Cu(P2O7)2. 6- Complex ions cannot exist stably in the electrolyte; instead, they will form copper pyrophosphate precipitate or Cu precipitate in the electrolyte. 2+ This severely impacts work efficiency. Therefore, this invention requires strict pH control at 8.5~8.8 to ensure the formation of stable Cu(P2O7)2 in the electrolyte. 6- ion.
[0060] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for micro-arc oxidation of a titanium-based pollution control device, characterized by, The method comprises the following steps: Cu(P2O7)2 6- The application discloses a method for preparing a copper-doped micro-arc oxidation film on a titanium-based workpiece, and belongs to the technical field of micro-arc oxidation. The titanium-based workpiece is a pollution discharge pipeline in a titanium-based pollution discharge equipment. Cu(P2O7)2 in the electrolyte 6- The concentration of the electrolyte is 0.005 mol / L to 0.05 mol / L, and the pH of the electrolyte is 8.5 to 8.
8.
2. The method of micro-arc oxidation of titanium-based sewage equipment according to claim 1, characterized in that, The concentrations of the components in the electrolyte are as follows: 0.01-0.02 mol / L copper pyrophosphate, 0.5-0.9 mol / L potassium pyrophosphate, 0.01-0.02 mol / L potassium phosphate, and 0.05-0.06 mol / L sodium dihydrogen phosphate. The electrolyte further comprises sodium hydrogen phosphate, and the pH value of the electrolyte is 8.5-8.
8.
3. The method of micro-arc oxidation of titanium-based sewage equipment according to claim 2, characterized in that, When the material of the titanium-based workpiece is TC4, the concentrations of the components in the electrolyte are as follows: 0.01 mol / L copper pyrophosphate, 0.5 mol / L potassium pyrophosphate, 0.01 mol / L potassium phosphate, and 0.05 mol / L sodium dihydrogen phosphate.
4. The method of micro-arc oxidation of titanium-based sewage equipment according to claim 2, characterized in that, When the material of the titanium-based workpiece is TA1, the concentrations of the components in the electrolyte are as follows: 0.02 mol / L copper pyrophosphate, 0.56 mol / L potassium pyrophosphate, 0.01 mol / L potassium phosphate, and 0.06 mol / L sodium dihydrogen phosphate.
5. The method of micro-arc oxidation of titanium-based sewage equipment according to claim 2, characterized in that, When the material of the titanium-based workpiece is TA3, the concentrations of the components in the electrolyte are as follows: 0.02 mol / L copper pyrophosphate, 0.90 mol / L potassium pyrophosphate, 0.02 mol / L potassium phosphate, and 0.06 mol / L sodium dihydrogen phosphate.
6. The method of micro-arc oxidation of titanium-based sewage equipment according to claim 1, characterized in that, The parameters of the micro-arc oxidation are as follows: working voltage is 400V-800V, working frequency is 100Hz-1000Hz, current density is 0.02A / cm 2 ~0.80A / cm 2 , duty cycle is 10%-60%, processing time is 5min-30min, and reaction temperature is 10℃-50℃.
7. The method of micro-arc oxidation of titanium-based sewage equipment according to claim 2, characterized in that, The material of the titanium-based workpiece further comprises TA2, Ti-Ni, Ti-2Al-2.5Zr, Ti-32Mo and Ti-Mo-Ni.
8. The method of micro-arc oxidation of titanium-based sewage equipment according to claim 1, characterized in that, Before the titanium-based workpiece is subjected to micro-arc oxidation, the titanium-based workpiece is further subjected to the following steps: degreasing, polishing, cleaning and drying.
9. The method of micro-arc oxidation of titanium-based sewage equipment according to claim 1, characterized in that, The inert electrode is any one of a platinum sheet, graphite and stainless steel.
10. The method of micro-arc oxidation of titanium-based sewage equipment according to claim 1, characterized in that, The distance between the anode and the cathode is 3-20 cm.